Compliance in Review Attendance among Orthodontic Patients attending a Tertiary Level Health Care Centre - O.T. Temisanren; J.U. Ifesanya; A.B. Olatunji (Nigerian Dental Association, 2020)
Objectives: Estimating patient compliance during orthodontic treatment cannot be overemphasized as timely and successful outcome of orthodontic treatment is dependent on it. This study assessed patients' compliance to orthodontic reviews at a tertiary care orthodontic clinic as well as explored various factors that may influence review attendance. Materials and Methods: Data were collected retrospectively from 133 patients' case notes as well as the clinic daily attendance records. Socio-demographic data and type of appliance used by patients was extracted. The pattern of punctuality (in days) to clinic attendance as prescribed by the managing orthodontist was also ascertained. Data were analysed using the SPSS version 22. Level of significance was set at p<0.05. Results: The mean age was 14.65 ± 5.98 years. Sixty-two (46.6%) patients were males while 71(53.4%) were females. Sixteen patients (12%) had removable appliances, 116(87.2%) had fixed appliances while only one person (0.8%) had both fixed and removable appliances. Eighty (60.2%)  attendees were resident within the state of the clinic's location while 53 (39.8%) resided outside the state. At the first review visit after treatment commenced, 92(69.2%) presented on time for review while 41 (30.8%) defaulted with a mean lag time of 49.0±49.0 days before presenting at the clinic. The total default time varied significantly with the number of visits and length of treatment time (p<0.001). Conclusion: Rate of default to orthodontic reviews was found to increase gradually from the 2nd visit and imparted negatively on treatment time.